Microsoft SharePoint Server 2007 bible - Leon, Wynne (Wiley Pub., 2007)
Key topics discussed include creating an Office Server portal, content management, SharePoint server and business intelligence, Office Server customization, and solutions scenarios Expert advice covers how to use SharePoint to create collaborative Web sites that easily integrate with corporate intranets and portals, team and customer collaboration sites, document management systems, and more.